Towards Improved Hospital Services: IS/IT Strategic Recommendations for Muhammadiyah Hospital Based on Cost and Prioritization Analysis: Menuju Peningkatan Pelayanan Rumah Sakit: Rekomendasi Strategis IS/IT untuk Rumah Sakit Muhammadiyah Berdasarkan Analisis Biaya dan Prioritas - Ambarwati, Rita; Bintang Pamungkas, Moch. Ridho (Universitas Muhammadiyah Sidoarjo, 2024)
This mixed-method study looks into the strategic priorities of information systems and technology (IS/IT) at Muhammadiyah Hospital in Sidoarjo, with a focus on long-term goals and alternative tactics. Using the Ward and Peppard approach, the research seeks to develop strategic suggestions and identify potential future application portfolios. The data was examined using cost-benefit analysis (CBA) and ranked using the Analytical Hierarchy Process. Furthermore, professional viewpoints were acquired through focus group discussions to evaluate IS/IT portfolio recommendations. The findings show that cost parameters play an important role in selecting developmental systems. The study emphasizes the need of using a multi-method approach in IS/IT strategic planning within healthcare, as well as the value of expert input in making good decisions. The findings provide a framework for Muhammadiyah Hospital to improve future services and go forward with key IS/IT projects.